Geographic Information Science and Remote Sensing in Management of Rare and Endangered Plant Species of Meghalaya - Bala Krishna Reddy, M. (Indian Forester, 2010)
Geographic Information Science (GIS), when used in combination with remote sensing provides a useful tool for mapping and management of rare and endangered plant species in Meghalaya, India which is a biodiversity hot spot region. The first step in this exercise is creation of polygon wise forest management inventory that would comprise details of threatened and endemic species in the area along with habitat conditions viz vegetation type, forest cover class apart from the stand characteristics namely wood volume etc. The second step is to overlay such polygons on land use classification map generated from remote sensing imageries through visual interpretation technique. Such a map created in ESRI Arc MAP would be useful to resource managers for outlining the present and future management plans towards conservation of a biodiversity rich region. A supplemental tool in this managerial exercise is visual polygon decomposition technique that provides precise information on the state of habitat and vegetation cover preservation apart from the trend it is likely to follow in the near future. Such an analysis is indispensable in areas like Jaintia hills district of Meghalaya where industrial citing activity has just begun exerting severe anthropogenic pressure on hitherto virgin habitat.